Waveform Distortion of Gaussian Beam in Atmospheric Turbulence Simulated by Phase Screen Method - Zhi-Qiang Yang; Li-hong Yang; Lei Gong; Liguo Wang; Xinyi Wang (Journal of Mathematics)
The atmospheric turbulence phase screen is generated based on the power spectrum inversion method, and the multiple transmission processes are statistically averaged. The waveform distortion of the Gaussian beam in the atmospheric turbulence is analyzed; the simulation results show that the property of Gaussian beam has been destroyed after its passing through the atmospheric turbulence. When the beam waist radius is close to a certain radius, the degree of change becomes larger. When it approaches the critical value, the wave surface no longer changes sharply, and as the turbulence intensity increases, the phase fluctuation becomes more and more severe, the coherence of the beam is destroyed, and the spot may be split into several pieces. Finally, the relationship of intensity fluctuation, amplitude fluctuation, and bit error rate with distance is analyzed.